Distribution Power Loss Minimization via Distributed Generation, Capacitor and Network Reconfiguration - Mohd Nabil Bin Muhtazaruddin; Nurul Aini Bani; Siti Armiza Mohd Aris; Hazilah Mad Kaidi; Abdul Yasser Abd Fatah; Jasrul Jamani Jamia; Firdaus Muhammad-Sukki; Siti Hawa Abu-Bakar (Institute of Advanced Engineering and Science, 2017)
This paper presents a solution to solve the network reconfiguration, DG coordination (location and size) and capacitor coordination (location and size), simultaneously. The proposed solution will be determined by using Artificial Bee Colony (ABC). Various case studies are presented to see the impact on the test system, in term of power loss reduction and also voltage profiles. The proposed approach is applied to a 33-bus test system and simulate by using MATLAB programming. The simulation results show that combination of DG, capacitor and network reconfiguration gives a positive impact on total power losses minimization as well as voltage profile improvement compared to other case studies.